Penerapan Metode Quranuna Untuk Meningkatkan Kemampuan Siswa Menghapal Al-Qur'an Pada Program Tahfidz Dan Baca Tulis Al-Qur'an - Nurhasan Nurhasan (Peneliti.net, 2022)
This research focused on the tahfidz Al Qur`an program including institution profiles, background, vision and mission, and planning the pattern of learning tahfidz and reading and writing the Qur`an using the Quranuna method. The process of implementing the Quranuna method includes the learning process in the classroom starting from the opening, the process of memorizing classically with the standard rhythm of the Quranuna method, and evaluation in the form of rote tests and group learning processes. This study uses a qualitative approach with descriptive methods with data collection techniques including observation, interviews, tests, documentation, and literature study. While data analysis uses data reduction (data reduction), data presentation (data display) and verification (conclusion drawing). The results showed that the results obtained in the application of the Quranuna method by using a test were that in general students got a score of